What value is the CINAHL database when searching for systematic reviews of qualitative studies?. Issue 1 (December 2015) - Wright, Kath; Golder, Su; Lewis-Light, Kate
Abstract Background The Cumulative Index to Nursing and Allied Health Literature (CINAHL) is generally thought to be a good source to search when conducting a review of qualitative evidence. Case studies have suggested that using CINAHL could be essential for reviews of qualitative studies covering topics in the nursing field, but it is unclear whether this can be extended more generally to reviews of qualitative studies in other topic areas. Methods We carried out a retrospective analysis of a sample of systematic reviews of qualitative studies to investigate CINAHL's potential contribution to identifying the evidence. In particular, we planned to identify the percentage of included studies available in CINAHL and the percentage of the included studies unique to the CINAHL database. After screening 58 qualitative systematic reviews identified from the Database of Abstracts of Reviews of Effects (DARE), we created a sample set of 43 reviews covering a range of topics including patient experience of both illnesses and interventions. Results For all 43 reviews (21 %) in our sample, we found that some of the included studies were available in CINAHL. For nine of these reviews, all the studies that had been included in the final synthesis were available in the CINAHL database, so it could have been possible to identify all the included studies using just this one database, while for an additional 21 reviews (49 %), 80 % or more of the included studies were available in CINAHL. Consequently, for a total of 30 reviews, or 70 % of our sample, 80 % or more of the studies could be identified using CINAHL alone. 11 reviews, where we were able to recheck all the databases used by the original review authors, had included a study that was uniquely identified from the CINAHL database. The median % of unique studies was 9.09 %; while the range had a lowest value of 5.0 % to the highest value of 33.0 %. Conclusions Assuming a rigorous search strategy was used and the records sought were accurately indexed, we could expect CINAHL to be a good source of primary studies for qualitative evidence syntheses. While we found some indication that CINAHL had the potential to provide unique studies for systematic reviews, we could only fully test this on a limited number of reviews, so we are less confident about this finding.